Frijol Tepari: cultivo nutritivo y resistente a la sequia para la adptacion climatica en Mesoamerica - Bioversity International; Universidad del Valle (2017)
Tepary bean (Phaseolus acutifolius) is a legume crop that originated in the southwestern USA and central Mexico and is grown as far south as El Salvador. Today most tepary bean is produced by subsistence farmers for household consumption but wider use of this crop has potential to support climate change adaptation of Mesoamerican farm systems. This fact sheet outlines the features of this underutilized species with special attention to its role in nutrition and climate sensitive agriculture.